Associations of Fully Automated CSF and Novel Plasma Biomarkers With Alzheimer Disease Neuropathology at Autopsy - Grothe Michel J; Moscoso Alexis; Ashton Nicholas J; Karikari Thomas K; Lantero-Rodriguez Juan; Snellman Anniina; Zetterberg Henrik; Blennow Kaj; Schöll Michael; Alzheimer’s Disease Neuroimaging Initiative (Wolters Kluwer, 2022)
Objective: To study cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD) analyzed by fully automated Elecsys immunoassays in comparison to neuropathologic gold standards, and compare their accuracy to plasma phosphorylated tau (p-tau181) measured using a novel Simoa method.
Methods: We studied ante-mortem Elecsys-derived CSF biomarkers in 45 individuals who underwent standardized post-mortem assessments of AD and non-AD neuropathologic changes at autopsy. In a subset of 26 participants, we also analysed ante-mortem levels of plasma p-tau181 and neurofilament light (NfL). Reference biomarker values were obtained from 146 amyloid-PET-negative healthy controls (HC).
Results: All CSF biomarkers clearly distinguished pathology-confirmed AD dementia (N=27) from HC (AUCs=0.86-1.00). CSF total-tau (t-tau), p-tau181, and their ratios with Aβ1-42, also accurately distinguished pathology-confirmed AD from non-AD dementia (N=8; AUCs=0.94-0.97). In pathology-specific analyses, intermediate-to-high Thal amyloid phases were best detected by CSF Aβ1-42 (AUC[95% CI]=0.91[0.81-1]), while intermediate-to-high CERAD neuritic plaques and Braak tau stages were best detected by CSF p-tau181 (AUC=0.89[0.79-0.99] and 0.88[0.77-0.99], respectively). Optimal Elecsys biomarker cut-offs were derived at 1097/229/19 pg/ml for Aβ1-42, t-tau, and p-tau181. In the plasma subsample, both plasma p-tau181 (AUC=0.91[0.86-0.96]) and NfL (AUC=0.93[0.87-0.99]) accurately distinguished pathology-confirmed AD (N=14) from HC. However, only p-tau181 distinguished AD from non-AD dementia cases (N=4; AUC=0.96[0.88-1.00]), and showed a similar, though weaker, pathologic specificity for neuritic plaques (AUC=0.75[0.52-0.98]) and Braak stage (AUC=0.71[0.44-0.98]) as CSF p-tau181.
Conclusions: Elecsys-derived CSF biomarkers detect AD neuropathologic changes with very high discriminative accuracy in-vivo. Preliminary findings support the use of plasma p-tau181 as an easily accessible and scalable biomarker of AD pathology.